The politics of intolerance - Irish style - O'Donnell, Ian (The British journal of criminology, 2003)
The law and order' debate in the Republic of Ireland has taken a number of unusual twists in recent years, developments that are not widely recognized and have generated little academic interest outside the country. The absence of an Irish voice in the international literature is striking. A country with a traditionally low level of crime, Ireland has witnessed a sharp decrease in the official crime rate since 1995. The murders of a police officer and journalist in 1996 led to a transformation of the criminal justice landscape. A major prison-building programme was initiated, a policy of zero tolerance' policing was introduced, and some of the symptoms of a culture of control' began to emerge